2014
DOI: 10.1186/s13023-014-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide patient registry for GNE myopathy in Japan

Abstract: BackgroundGNE myopathy is a slowly progressive autosomal recessive myopathy caused by mutations in the GNE (glucosamine (UDP-N-acetyl)-2-epimerase/N-acetylmannosamine kinase) gene. This study aimed to (1) develop a nationwide patient registry for GNE myopathy in order to facilitate the planning of clinical trials and recruitment of candidates, and (2) gain further insight into the disease for the purpose of improving therapy and care.MethodsMedical records of genetically-confirmed patients with GNE myopathy at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 20 publications
2
64
0
Order By: Relevance
“…Cardiac involvement has been reported in a mouse model of GNE myopathy [21] but is not usually seen in patients. As part of the Japanese Registry of GNE myopathy, all 35 subjects who had an echocardiogram had normal cardiac function [22]. A cohort of Bulgarian Roma patients had cardiac abnormalities detected by electrocardiogram (EKG) (n = 12) or echocardiogram (n = 33), but most of these were subclinical or due to other predisposing factors [20].…”
Section: Clinical Manifestations Of Gne Myopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac involvement has been reported in a mouse model of GNE myopathy [21] but is not usually seen in patients. As part of the Japanese Registry of GNE myopathy, all 35 subjects who had an echocardiogram had normal cardiac function [22]. A cohort of Bulgarian Roma patients had cardiac abnormalities detected by electrocardiogram (EKG) (n = 12) or echocardiogram (n = 33), but most of these were subclinical or due to other predisposing factors [20].…”
Section: Clinical Manifestations Of Gne Myopathymentioning
confidence: 99%
“…Thrombocytopenia has been reported in a small number of patients with GNE myopathy [25,26], but one study determined the occurrence of thrombocytopenia was similar to that of the general population in Japan [10,22]. Congenital thrombocytopenia has also been reported in families with compound heterozygous GNE mutations, and although the etiology still needs to be determined, the authors suggested hyposialylation of platelets leading to increased platelet clearance as a possible mechanism [26,27].…”
Section: Clinical Manifestations Of Gne Myopathymentioning
confidence: 99%
“…However, these two are industry funded and thus any natural history study on VCP will have to have adequate funding to support such aims. Perhaps these can be run under the umbrella of TREAT-MND ALLIANCE, as exemplified by the Japanese GNE myopathy study [65]. Such a natural history study should address the current gaps, including natural history of the disease, variability in interfamilial as well as intrafamilial phenotypes, and provide phenotype–genotype correlations, information about disease modifiers and helpful biomarkers in the disease.…”
Section: Session 5 – Natural History and Management Of Vcp Diseasementioning
confidence: 99%
“…It is a rare, recessively inherited, early adult‐onset myopathy . It is typically characterized by slow progression that preferentially affects the tibialis anterior muscles, commonly spares the quadriceps femoris muscles and gradually spreads to other muscles . GNE myopathy occurs worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is typically characterized by slow progression that preferentially affects the tibialis anterior muscles, commonly spares the quadriceps femoris muscles and gradually spreads to other muscles. 2,3 GNE myopathy occurs worldwide. The prevalence ranges from 1/1 000 000 to 21/ 1 000 000, although it may be underestimated as many patients escape diagnosis.…”
Section: Introductionmentioning
confidence: 99%